Domestic wastewater treatment with Fenton and Constructed Wetlands system - Marcionilio, Suzana Maria Loures de Oliveira; Gadêlha, José Eduardo Ferreira da Silva; Carvalho, Vicente Douglas Figueredo; Costa, Adriano Carvalho; Júnior, Édio Damásio da Silva (Seven Editora, 2024)
Alternative forms of domestic sewage treatments, such as Constructed Wetlands (WC) systems, are efficient and environmentally friendly. This effect can be intensified by associating two treatments to reduce the pollutant load, in this work, combined the Fenton reaction after a WC system for the removal of Organic Matter (OM). The experimental assay was carried out in a 5 x 5 factorial arrangement, with the factors beingH2O2 and Fe²+ at concentrations at both 0, 25, 50, 75 and 100 %, and the variable response was OM at UV 254nm. The data were submitted to exploratory analysis, considering the effects of the factors and their interactions, performing the analysis of variance and statistical models Linear, Linear Plateau, quadratic and quadratic Plateau. There was an interaction between the factors, unfolding Fe²+ within H2O2, it was found that in all H2O2 concentrations, the plateau model was the one that best fitted. While in the unfolding H2O2 within Fe²+ it was found that in concentrations up to 50% of Fe²+ the quadratic model was better adjusted, while in the highest concentrations (75 and 100%) it was the plateau. Modeling demonstrated that the optimal dosage for this study is 25% H2O2 (250 mg L-1) / 33% Fe3+ (165 mg L-1), removing 92.75% OM. DOI:https://doi.org/10.56238/sevened2024.007-040